The problem of formation of artistic and professional skills in the process of training educational teachers in the arts in higher educational institutions (Pedagogy of Higher and Secondary Education, 2009)
Thu article is devoted a question of training future visual arts teachers. Here are (unsized features of formation art abilities in the process of professional students training in visual- pedagogical specialities.